Information Pollution in a Digital and Polarized World as a Challenge to Human Rights Protection – the Council of Europe’s Approach - Jaskiernia, Alicja (Review of European and Comparative Law, 2021)
Information pollution in a digitally connected and increasingly polarized world, the spread of disinformation campaigns aimed at shaping public opinion, trends of foreign electoral interference and manipulation, as well as abusive behaviour and the intensification of hate speech on the internet and social media are the phenomenon which concern international public opinion. These all represent a challenge for democracy, and in particular for the electoral processes affecting the right to freedom of expression, including the right to receive information, and the right to free elections. It is a growing international effort to deal with these problems. Among international organizations engaged to seek solutions is the Council of Europe (CoE). The author analyses CoE’s instruments, legally binding (as European Convention on Human Rights), as well of the character of “soft law”, especially resolution of the CoE’s Parliamentary Assembly 2326 (2020) Democracy hacked? How to respond? She exposes the need for better cooperation of international organizations and states’ authorities in this matter.